Metaphoric Representations of Spirituality in Ebenezer Obey’s Music - Olayiwola, Mopelola Rachael; Olaniyan, Solomon Olusayo (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
This paper investigates the synergy that exists between metaphor and spirituality within the Yoruba cosmology as exemplified in the music of Ebenezer Obey. The study underscores the authenticating role metaphor plays in the concretisation of Yoruba beliefs in the existence of a supernatural world. The existing variations of independent studies on both concepts attest to the rich cognitive influence both ideologies evoke within the academia. However, most of the extant studies carried out on these concepts have mainly honed their distinctive strengths. The corpus of research on metaphor relates its relevance mainly to the academic sphere where it acts as diagnostic tool for the analysis of literary terms and by extension to specified human experiences and restricts its versatile application to the significant influence metaphor has on spirituality, thus, de-emphasising the strengthening potency the connection between both ideologies can have on the social and economic lives of people. This notion of irreconcilable difference has resulted in undermining the veritable possibility of an alignment between metaphor and spirituality. This is against the backdrop of paucity of scholarship on this creative hybridisation. This study, therefore, foregrounds the essence of this metaphorical appropriation on the Yoruba ability to re-interpret their disillusioned post-independence realities. Conceptual metaphor theory is deployed as a tool by which underlying metaphor of spirituality is pointed out in the selected music texts of Ebenezer Obey.